Taxonomic study of Central Asian species of the genus Macropsis Lewis, 1836 (Homoptera: Auchenorrhyncha: Cicadellidae: Macropsinae). I: Redescriptions of willow-dwelling species from West Tien Shan Mountains - Tishechkin, Dmitri Yu. (Zootaxa, 2013)
Macropsis abdullaevi Dubovskiy, 1966 = M. arslanbobica Dlabola, 1967 syn. nov., M. ibragimovi Dubovskiy, 1966 and M. asiatica Dubovskiy, 1966 from West Tien Shan Mts. (Kyrgyzstan) are redescribed and illustrated based on material from type localities or/and adjacent territories. M. tarbagataica Mityaev, 1971 from Kazakhstan is recorded from West Tien Shan for the first time. Data on host plants and male vibrational calling signals for all species considered are provided.